Hubungan Status Sosial Ekonomi dan Sikap Lingkungan Terhadap Perilaku Hidup Bersih dan Sehat (PHBS) di Kecamatan Awangpone Kabupaten Bone - Rosmawati Rosmawati; Firdaus Daud; Muhammad Danial (Universitas Negeri Makassar, 2022)
This research is a correlational quantitative descriptive research that aims to determine the relationship between socio-economic status and environmental attitudes towards clean living behavior (PHBS) in Awangpone District, Bone Regency, the independent variable in this study is Socio-Economic Status, while the dependent variable is clean living behavior and healthy. The population in this study was the people of Awangpone District, Bone Regency. Data collection techniques using a questionnaire. The data analysis technique is descriptive analysis and inferential analysis. Based on the results of inferential data analysis, it was found that there was a positive and significant relationship between environmental attitudes and clean and healthy living behavior at the level of a very strong relationship. Socioeconomic status with clean and healthy living behavior has a positive and significant relationship. Socio-economic status with clean and healthy living behavior is at a very strong relationship level. The biggest effective contribution to the dependent variable (Clean and Healthy Living Behavior) is given by socioeconomic status 34.0% and environmental attitude 51.3%. The total effective contribution is 85.3%, which means that socio-economic status and environmental attitudes together provide an effective contribution of 85.3% to the clean and healthy living behavior of the Awangpone sub-district, Bone district, while 14.7% is influenced by factors not examined.